ANALISIS POLA PERUBAHAN PENGGUNAAN LAHAN PERTANIAN KE NON PERTANIAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA DI KOTA MATARAM, 2007-2012 - , Tati Atmayanti ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aimed to analysis the influence of factors that affect the change pattern of use of agriculture land leading to non agriculture and impact to price of land in Mataram City. This is important, because of increasing conversion of agriculture impacted urban growth. This study used land map in 2010 and 2011 according to RT/RW of Mataram City in 2011-2031. Independent variable used were population, Gross Domestic Regional Product (GDP) and number of trade company. Otherwise, Dependent variable used was large agriculture land which conversion. The data used secondary data obtained from the relevant departement. The research was analyzed by using quantitative descriptive method. The instrument of Analysis data used Geographic Information System (GIS) with regression panel data and overlay method. The result of this research showed that the change of use of agriculture land pattern to non agriculture lead to Central Business District (CBD), public facilities and social facilities. The impact from change of use of agriculture land was increasing price of land. The population negative affect and Gross Domestic Regional Product (GDP) negative significant affected the amount large of agriculture land, while number of trade company negative affected the amount large agriculture land, but it is not significant. However, over all third significant variables affected the amount large of agriculture land.